Transient Hearing Loss and Objective Tinnitus Induced by Mouth Opening: A Rare Connection Between the Temporomandibular Joint and Middle Ear Space. Issue 7 (August 2016) - Hidaka, Hiroshi; Tatewaki, Yasuko; Sakamoto, Maya; Kobayashi, Toshimitsu; Yuasa, Yu; Yuasa, Ryo; Nomura, Kazuhiro; Yamauchi, Daisuke; Katori, Yukio
Abstract : Supplemental Digital Content is available in the text Abstract : Objectives: To describe objective tinnitus complicated with transient low-tone hearing loss coinciding with mouth opening, which was related to the connection between the mandibular fossa and middle ear space. Patients: A 41-year-old man presented with tinnitus, ear fullness, and hearing loss in the left ear on mouth opening. Main Outcome Measures: Clinical case records, audiological data, and radiological analyses including computed tomography (CT) and magnetic resonance imaging. Results: Hearing thresholds on the affected side, which were evaluated with mouth opening, showed elevations of approximately 20 dB in the frequencies below 1000 Hz. Again, peak pressure on the tympanogram deviated negatively to −220 mmH2 O under mouth opening without changing peak amplitude. CT showed a connection between the mandibular fossa and middle ear space, as revealed by a gas collection around the joint capsule evaluated in two phases (with and without mouth closing). Ear symptoms resolved after myringotomy. Conclusions: Although an influence of temporomandibular disorder (TMD) on tinnitus perception has been debated, whether this association is causal or fortuitous has remained contentious. The present case showed a unique feature of tinnitus attributed to a connection between the mandibular fossa and middle ear space.